The impact of emotional dysregulation and comorbid depressive symptoms on clinical features, brain arousal, and treatment response in adults with ADHD - Huang, Jue; Mauche, Nicole; Ahlers, Eike; Bogatsch, Holger; Böhme, Pierre; Ethofer, Thomas; Fallgatter, Andreas J; Gallinat, Jürgen; Hegerl, Ulrich; Heuser, Isabella; Hoffmann, Knut; Kittel-Schneider, Sarah; et al. (Frontiers in Psychiatry, 2024)
The role of emotional dysregulation (ED) in Attention-deficit/hyperactivity disorder (ADHD) has become an important issue. This study, in which we analyzed data from a predictive pharmaco-EEG-trial, aimed to examine whether symptoms of ED in adult ADHD affect ADHD symptom severity, brain arousal regulation as measured by resting EEG and the response to stimulant medication. ED was defined as having a sex- and age-corrected T-score > 70 on the emotional lability subscale of the German version of the Conners' Adult ADHD Rating Scale. A total of 115 participants were included in the study, 56 of whom had ED. Participants with ED were more impaired in terms of severity of core ADHD symptoms, especially inattentive symptoms, comorbid depressive symptoms, interpersonal relationships, and quality of life. In addition, participants with ED were more likely to report a total score above 13 on the Beck Depression Inventory-II, which was considered to be the cut-off for mild depression. No differences were found between the ED and non-ED groups in response to stimulant medication or in brain arousal regulation. In addition, there was no significant effect of ED with comorbid depressive symptoms on treatment response. There was a trend for subgroups who showed a change in brain arousal regulation associated with symptom improvement. Our findings may support the assumption that ED may be an important feature of ADHD. The use of EEG-based brain arousal regulation as a diagnostic and predictive tool in ADHD in the presence of ED and comorbid depressive symptoms should be further investigated.